Can the Core of Icelanders be Found in the Wilderness?:: The Representation of Iceland and Icelanders in the Film Heima by Sigur Rós - Hall, Þorbjörg Daphne (European Journal of Musicology, 2020)
This article investigates how Iceland is presented inHeima: A Film by Sigur Rósand how it relates to the issues of nationalism and national identity in Iceland.In this article stereotypes of the North and Iceland are introduced, and concerns regarding nature and nationalism are presented. The indie band Sigur Rós and the film are discussed, and the relationship between nature and music and their conjunction is analysed. The stereotypes of Icelandic national identity appearing in the film are examined and put in context with the ideas from the national romantic movement and its modern counterparts. This is likewise intertwined with an analysis of the attitudes towards nature conservation in the film. The findings show how the film can be understood as a contribution to nation building based on an “othering” process constructed on stereotypes and nationalism, which originates from both urban and foreign viewpoints. This article investigates how Iceland is presented inHeima: A Film by Sigur Rósand how it relates to the issues of nationalism and national identity in Iceland.In this article stereotypes of the North and Iceland are introduced, and concerns regarding nature and nationalism are presented. The indie band Sigur Rós and the film are discussed, and the relationship between nature and music and their conjunction is analysed. The stereotypes of Icelandic national identity appearing in the film are examined and put in context with the ideas from the national romantic movement and its modern counterparts. This is likewise intertwined with an analysis of the attitudes towards nature conservation in the film. The findings show how the film can be understood as a contribution to nation building based on an “othering” process constructed on stereotypes and nationalism, which originates from both urban and foreign viewpoints.